Digital Entrepreneurship in Brazil: Insights From The Digital Platform Economy Index Analysis - Kusumaningrum, Sita Dewi; Wibisono, Eristian (STI Policy and Management Journal, 2024)
Digital Entrepreneurship Ecosystem (DEE) integrates the concepts of Digital Ecosystem (DE) and Entrepreneurship Ecosystem (EE). Developed over the last decade, research and application of DEE in developing countries remains limited. In this paper, we use a DEE in the form of the Digital Platform Economy (DPE) index, which measures the state of DEE in 116 countries, taking Brazil as a case study and comparing it with two benchmark countries (Uruguay and Argentina) that are members of the MERCOSUR group of economies. Through a five-step structured analysis, we first examine the general condition of Brazil's DEE in terms of development and then analyze the derived components of the DPE index to find the strengths and weaknesses of Brazil's DEE compared to the two benchmark countries. The results show a healthy balance between DE and EE in Brazil. However, through further analysis using the Penalty for Bottleneck (PFB) method, we recommend four main pillars of DEE, namely digital literacy, digital openness, digital adoption, and digital access, to maintain the balance between DE and EE and improve Brazil's DEE. Our results contribute to the development of DEE literature and promote DEE evaluation methods as a way to recommend DEE development in developing countries. Keywords: Digital entrepreneurship, DPE index, digital ecosystem, entrepreneurial ecosystem.